Modeling epithelial-mesenchymal transition in patient-derived breast cancer organoids - Bar-Hai, Neta; Ben-Yishay, Rakefet; Arbili-Yarhi, Sheli; Herman, Naama; Avidan-Noy, Vered; Menes, Tehillah; Mansour, Aiham; Awwad, Fahim; Balint-Lahat, Nora; Goldinger, Gil; Hout-Siloni, Goni; Adileh, Mohammad; et al. (Frontiers in Oncology, 2024)
Cellular plasticity is enhanced by dedifferentiation processes such as epithelial-mesenchymal transition (EMT). The dynamic and transient nature of EMT-like processes challenges the investigation of cell plasticity in patient-derived breast cancer models. Here, we utilized patient-derived organoids (PDOs) as a model to study the susceptibility of primary breast cancer cells to EMT. Upon induction with TGF-β, PDOs exhibited EMT-like features, including morphological changes, E-cadherin downregulation and cytoskeletal reorganization, leading to an invasive phenotype. Image analysis and the integration of deep learning algorithms enabled the implantation of microscopy-based quantifications demonstrating repetitive results between organoid lines from different breast cancer patients. Interestingly, epithelial plasticity was also expressed in terms of alterations in luminal and myoepithelial distribution upon TGF-β induction. The effective modeling of dynamic processes such as EMT in organoids and their characteristic spatial diversity highlight their potential to advance research on cancer cell plasticity in cancer patients.